Abundance in Sewage of Bacteriophages That Infect Escherichia coli O157:H7 and That Carry the Shiga Toxin 2 Gene - Muniesa, Maite (American Society for Microbiology, 1998)
Shiga toxin-converting bacteriophages are involved in the pathogenicity of some enteric bacteria, such as Escherichia coli O157:H7, but data on the occurrence and distribution of such phages as free particles in nature were not available. An experimental approach has been developed to detect the presence of the Shiga toxin 2 (Stx 2)-encoding bacteriophages in sewage. The Stx 2 gene was amplified by PCR from phages concentrated from 10-ml samples of sewage. Moreover, the phages carrying the Stx 2 gene were detected in supernatants from bacteriophage enrichment cultures by using an Stx 2-negative E. coli O157:H7 strain infected with phages purified from volumes of sewage as small as 0.02 ml. Additionally, the A subunit of Stx 2 was detected in the supernatants of the bacteriophage enrichment cultures, which also showed cytotoxic activity for Vero cells. By enrichment of phages concentrated from different volumes of sewage and applying the most-probable-number technique, it was estimated that the number of phages infectious for E. coli O157:H7 and carrying the Stx 2 gene was in the range of 1 to 10 per ml of sewage from two different origins. These values were approximately 1% of all phages infecting E. coli O157:H7.